Challenges and Opportunities in Implementing Green Building Materials in Malaysia - Siganul, Aimie Peace; Puspitasari, Surya Dewi (Civil and Sustainable Urban Engineering, 2025)
Sustainable construction is essential for minimizing greenhouse gas emissions, reducing waste, and promoting cost efficiency. However, Malaysia faces persistent challenges in environmental management, development approval procedures, and the adoption of green technologies. While various studies have explored individual aspects of sustainability in construction, there remains a lack of comprehensive reviews that critically assess how regulatory frameworks, approval processes, and green technologies intersect to influence sustainable construction outcomes in the Malaysian context. This review addresses that gap by synthesizing current practices, identifying key bottlenecks, and proposing actionable strategies for improvement. It evaluates regulatory frameworks, environmental strategies, green materials, and advanced technologies that support sustainable construction. The efficiency of the development approval process including project proposals, land acquisition, planning approval, occupancy, and handover plays a crucial role in enabling sustainable outcomes. Green technologies such as renewable energy, solar power, and smart construction techniques like the Internet of Things (IoT) are examined for their potential to enhance sustainability. The review also highlights persistent gaps in cost management and regulatory enforcement. By consolidating diverse strands of knowledge, this paper contributes to a clearer understanding of systemic barriers and opportunities within Malaysia’s sustainable construction landscape, offering policy and practice recommendations to guide future progress.